Pengukuran Konsep Efektivitas Sistem Informasi: Penelitian Pendahuluan - Endah Widowati; Didi Achjari (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Previous studies provide information system effectiveness measures. The current studyattempts to validate these measures in the Indonesian context. Based on the ReformulatedDeLone and McLean IS Success Model, this study conducted factor analysis to obtain a numberof underlying factors as well as items included in the model. The study that was administeredusing questionnaire survey concluded that there are some exogenous variables to explainnet benefits obtained from implementing an information system, for instance managementprocess, information existence, individual actualization, and decision-making effectiveness.Keywords: IS effectiveness, factor analysis, net benefits, IT satisfaction.